Room Temperature In-Situ Synthesis of Inorganic Lead Halide Perovskite Nanocrystals Sol Using Ultraviolet Polymerized Acrylic Monomers as Solvent and Their Composites with High Stability - Ludan Zhu; Shuanglong Yuan; Jun Cheng; Long Chen; Chuanqi Liu; Hua Tong; Huidan Zeng; Qiling Cheng (Applied Sciences, 2020)
As a kind of promising optoelectrical material, all-inorganic perovskite nanocrystals CsPbX3 (X = Cl, Br, I) have attracted much attention, due to their excellent optoelectrical characteristics, in recent years. However, their synthesis approaches require rigorous conditions, including high temperature, eco-unfriendly solvent or complex post-synthesis process. Herein, to overcome these issues, we reported a novel facile room temperature in-situ strategy using ultraviolet polymerizable acrylic monomer as solvent to synthesis CsPbX3 nanocrystals without a complex post-synthesis process. In this strategy, adequate soluble precursors of Cs, Pb and Br and reaction terminating agent 3-aminopropyltriethoxysilane (APTES) were used. The obtained CsPbBr3 nanocrystals showed a high photoluminescence quantum yields (PLQY) of 87.5%. The corresponding polymer composites, by adding light initiator and oligomer under ultraviolet light radiation, performed excellent stability in light, air, moisture and high temperature. The reaction process and the effect of the reaction terminating agent have been investigated in detail. This strategy is a universal one for synthesizing CsPbX3 nanocrystals covering visible light range by introducing HCl and ZnI2.